PENGARUH TEMUAN AUDIT DAN TINDAK LANJUT REKOMENDASI HASIL PEMERIKSAAN TERHADAP OPINI ATAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN/KOTA DI PRIVINSI ACEH - Rahmi, Maulidya; Ariani, Nita Erika (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This study aims to determine the effect of the rest of the audit findings and follow-up of the audit results on the opinion of local government financial report of the regency/city government in Aceh Province. The population in this study is all 23 regencies/cities in Aceh Province. Samples are selected by using saturated or census sample techniques. The data source of this study cames from the secondary data obtained from the reports audit result of audi board of Indonesia for the 2015-2017 period. Analysis method used is ordinal logistic regression analysis. The results of this study indicate that the audit findings have a negative effect on opinion of local government finalcial report, and follow-up of the audit results have negative effect on opinion of local government financial report